An easy and scalable approach to synthesize three-dimensional sandwich-like Si/Polyaniline/Graphene nanoarchitecture anode for lithium ion batteries. Issue 4 (March 2018) - Huang, Rui-an; Guo, Yuzhong; Chen, Zhining; Zhang, Xingshuai; Wang, Jianhua; Yang, Bin
Abstract: A new three-dimensional (3D) sandwich-like Si/Polyaniline/Graphene nanoarchitecture anode for lithium ion batteries (LIBs) is successfully fabricated through an easy approach. In this nanoarchitecture, the in-situ polymerized electronic conductive polyaniline (PAni) hydrogel, acting as "glue", agglutinates tightly to both the silicon nanoparticles (SiNPs) and graphene sheets, forming efficient conductive networks with high elastic modulus and high tensile strength. This mechanically robust nanoarchitecture can endure the great volume change of silicon and retain structural stability during Li-ion insertion/extraction. The electrodes consisting of this 3D sandwich-like Si/Polyaniline/Graphene nanoarchitecture reveal excellent electrochemical performance. The progress made in this work provides an easy and scalable route for preparing Si-based anode materials with high performance for advanced LIBs.